Anti-immunoglobulin inhibits DNA synthesis in Epstein-Barr virus-transformed lymphoblastoid cell lines. - Gordon, J (1984)
Antibodies directed against immunoglobulin (anti-Ig) were found to inhibit the spontaneous incorporation of [3H]thymidine by Epstein-Barr virus (EBV) transformed lymphoblastoid cell lines (LCL). The degree of inhibition was variable but could exceed 80% following a 24 hr exposure of cells to anti-Ig. While a short pulse of antibody was sufficient to cause inhibition, maintainance of the effect required the continual presence of anti-Ig in culture. Maximal suppression by anti-Ig of [3H]thymidine uptake was reached between days 3 and 5, but cells eventually escaped from inhibition. For a line coexpressing IgM and IgD at the cell surfaces it was found that antibodies specific for the individual isotypes were equally effective at inducing suppression. Successful inhibition of DNA synthesis by F(ab')2 fragments of anti-Ig demonstrated that the Fc portion was not required for this effect. Anti-Ig immobilized on plastic surfaces was as effective as soluble antibody in inducing suppression. The implications of these findings for the generation of EBV-transformed LCL producing specific antibody are discussed.